Evolutionary Heuristic Computing Paradigm for 2D-DOA Estimation along Circular Array. (30th April 2022) - Shah, Fiaz Hussain; Raja, Muhammad Asif Zahoor; Al-Turjman, Fadi; Zaman, Fawad; Yang, Xiaodong
Abstract : Direction of arrival (DOA) estimation problem has growing interest for the researcher investigating in system identification models arising in the field of digital signal processing, mobile communication, controls, and beamforming. In the presented work, evolutionary heuristic computing paradigm is presented for 2D-DOA estimation of plane waves impinging on uniform circular array. Performance metric of mean squared error is utilized as construction of a fitness function for the system, and the optimization strength of three methodologies, genetic algorithms (GAs), Pattern Search (PS), and integration of GAs with PS (GA-PS) is exploited for 2D-DOA estimation based on elevation as well as azimuth angles. Consistent precision, convergence, stability, and robustness of integrated heuristics of GA-PS are endorsed through outcomes of statistical observations.